2013
DOI: 10.1089/dia.2012.0306
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adiponectin Helps to Differentiate Type 1 and Type 2 Diabetes Among Young Asian Indians

Abstract: Objective: This study assessed whether serum adiponectin could be used as a biochemical marker to differentiate type 1 diabetes mellitus (T1DM) from type 2 diabetes mellitus (T2DM) among young Asian Indians. Research Design and Methods: We recruited age-and sex-matched individuals with physician-diagnosed T1DM (n = 70) and T2DM (n = 72). All were 12-27 years of age with a duration of diabetes of >2 years, at a large tertiary-care diabetes center in Chennai, southern India. Age-and sex-matched individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…On the other hand, serum adiponectin was higher in T1DM and lower in T2DM, as compared to the group of subjects with normal glucose tolerance, so an adiponectin cut point of 5.1 µg/mL may be a useful tool for differentiating T1DM and T2DM, which is necessary for optimum treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, serum adiponectin was higher in T1DM and lower in T2DM, as compared to the group of subjects with normal glucose tolerance, so an adiponectin cut point of 5.1 µg/mL may be a useful tool for differentiating T1DM and T2DM, which is necessary for optimum treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In study that carried out in vitro showed that the adiponectin secretion was stimulated by insulin via phosphatidylinositol 3-kinase pathway [19] this signaling pathway stimulate both production and secretion of adiponectin hormone [20]. Several studies showed that higher serum adiponectin levels was reported in T1DM patients, specially patients surfing from diabetes complication like vascular complications or nephropathy [21]. The increased adiponectin concentration in patients with T1DM can interpreted as a response to posttranslational modifications (glycosylation) that exist in T1DM patients [22], decreased excretion due to renal failure [23], vascular injury [5], and impact of subcutaneous insulin therapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin may be capable of modulating the processes of lipid metabolism and regulating glucose ( 10 ). Abundant previous evidence has shown that the lack or dysfunction of adiponectin was proved to be intensely correlated with insulin resistance due to its characteristic as an insulin-sensitizing hormone ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%